Molecular and Epigenetic Impacts of Pesticides on the Female Reproductive System: A Review - Kamila Alawiyah; Dian Anggraini; Wildan Mubarok; Dwi Hardestyariki (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2024)
Pesticides, primarily originating from agricultural activities, have raised environmental and health concerns due to their suspected effects on the female reproductive system. Despite their widespread application, a significant research void exists concerning their implications for human female reproductive health. This review provides comprehensive information on the adverse effects of pesticides on female reproduction, focusing on their molecular and epigenetic mechanisms. In general, these adverse outcomes include ovarian dysfunction, hormonal irregularities, the onset of endometriosis, and an increased risk of stillbirths. From a mechanistic perspective, pesticides can interfere with the endocrine system, catalyze the formation of reactive oxygen species, and induce oxidative stress. At the molecular level, certain pesticides can act as hormone mimics, disrupting the normal hormonal balance. Moreover, they can trigger epigenetic shifts, leading to alterations in non-coding RNAs, histone configurations, and DNA methylation patterns. These epigenetic alterations not only have an immediate impact but can also be passed on to subsequent generations. Highlighting these concerns, this review underscores the urgent need for stringent regulations and aims to catalyze future in-depth studies on the relationship between pesticides and female reproductive health.